Direct demonstration of critical amino acid residues required for cytotoxic T-lymphocyte allorecognition of H-2 class I antigens. - McLaughlin-Taylor, E (1988)
To identify critical amino acid residues recognized by alloreactive cytolytic T lymphocytes (CTL) generated between H-2Kb and H-2Kbm1, we have derived a series of cloned L-cell lines expressing the following mutant H-2Kb class I genes. Cell line L-KbTyr-Tyr expresses a mutant gene in which positions 155-156 of the Kb molecule have been changed from Arg-Leu to Tyr-Tyr, leaving position 152 unchanged. Cell line L-KbAla expresses the reciprocal mutant gene that has position 152 of the Kb molecule mutated from glutamic acid to alanine, leaving positions 155-156 unchanged. Electrophoretic mobilities of the mutant Kb molecules reflect only those changes predicted by the mutations. Mutant-specific (anti-Kbm1) and native-specific (anti-Kb) CTL lyse L-KbTyr-Tyr and L-KbAla target cells equally well. Unlabeled target inhibition of lysis revealed a pattern of recognition and inhibition that suggests that the amino acid differences between Kbm1 and Kb create at least two discrete determinants that can be recognized by different populations of CTL. The results suggest that these determinants consist, at least in part, of a linear amino acid sequence from which critical amino acid residues can be identified.